2020
DOI: 10.1101/2020.05.04.20091272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spread of Covid-19 in the United States is controlled

Abstract: As of May 1, 2020, the number of cases of Covid-19 in the US passed 1, 062,446, interventions to slow down the spread of Covid-19 curtailed most social activities. Meanwhile, an economic crisis and resistance to the strict intervention measures are rising. Some researchers proposed intermittent social distancing that may drive the outbreak of Covid-19 into 2022. Questions arise about whether we should maintain or relax quarantine measures. We developed novel artificial intelligence and causal inference inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Official governmental regulations are possible resources for extracting features regarding the lockdown. Such features were examined for their association with infection rates in previous studies (Flaxman et al , 2020; Gatto et al , 2020; preprint: Hu et al , 2020; Li et al , 2020). However, the time governmental regulations were declared was often significantly different from the date social distancing initiated de facto (preprint: Kohanovski et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Official governmental regulations are possible resources for extracting features regarding the lockdown. Such features were examined for their association with infection rates in previous studies (Flaxman et al , 2020; Gatto et al , 2020; preprint: Hu et al , 2020; Li et al , 2020). However, the time governmental regulations were declared was often significantly different from the date social distancing initiated de facto (preprint: Kohanovski et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One could measure governmental regulations such as the permitted walking distance from the residence, limitations on mass gatherings, school closures, and whether people were allowed to attend their workplaces. For example, Hu et al (preprint: 2020) suggested a score that takes into account various governmental interventions in the United States. This score was used to predict future infections depending on the intervention level.…”
Section: Introductionmentioning
confidence: 99%
“…suggested a score that takes into account various governmental interventions in the United States 3 . This score was used to predict future infections depending on the intervention level.…”
Section: Introductionmentioning
confidence: 99%
“…One could measure governmental regulations such as the permitted walking distance from the residence, limitations on mass gatherings, school closures, and whether people were allowed to attend their workplaces. For example, Hu et al suggested a score that takes into account various governmental interventions in the United States 3 . This score was used to predict future infections depending on the intervention level.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, AI has been applied to predict outbreak like coronavirus. For example, an prediction model using AI to estimate the size, lengths and ending time of COVID-19 across China [130] . An auto-encoder is designed for modelling the transmission dynamics of the epidemic based on dataset collected from WHO sources.…”
Section: Ai-based Solutions For Coronavirus Fightingmentioning
confidence: 99%